Optimization of a novel series of N-phenylindoline-5-sulfonamide-based acyl CoA:monoacylglycerol acyltransferase-2 inhibitors: Mitigation of CYP3A4 time-dependent inhibition and phototoxic liabilities. Issue 15 (1st August 2015) - Sato, Kenjiro; Takahagi, Hiroki; Kubo, Osamu; Hidaka, Kousuke; Yoshikawa, Takeshi; Kamaura, Masahiro; Nakakariya, Masanori; Amano, Nobuyuki; Adachi, Ryutaro; Maki, Toshiyuki; Take, Kazumi; Takekawa, Shiro; et al.
Graphical abstract: A series of N -phenylindoline-5-sulfonamide derivatives was designed, synthesized, and evaluated as novel acyl CoA:monoacylglycerol acyltransferase-2 inhibitors for the treatment of obesity and metabolic disorders. Abstract: Acyl CoA:monoacylglycerol acyltransferase-2 (MGAT2) has emerged as a potential peripheral target for the treatment of obesity and metabolic disorders. We previously identified a novel series of N -phenylindoline-5-sulfonamide derivatives exemplified by 2 as potent and orally bioavailable MGAT2 inhibitors. Despite its attractive potency, further assessment revealed that this compound exhibited time-dependent inhibition (TDI) of cytochrome P450 3A4 (CYP3A4). To remove the undesirable CYP3A4 TDI activity, structural modification was focused on the 2, 4-difluoroaniline moiety on the basis of the assumption that this moiety would be involved in mechanism-based inhibition of CYP3A4 via oxidative metabolism. This led to the finding that the introduction of 4-chloro-2, 6-difluoroaniline significantly improved CYP3A4 TDI risk. Further optimization resulted in the discovery of N -(4-chloro-2, 6-difluorophenyl)-1-5-[1-methyl-3-(trifluoromethyl)-1 H -pyrazol-5-yl]pyrimidin-2-yl-7-(2-oxopyrrolidin-1-yl)-2, 3-dihydro-1 H -indole-5-sulfonamide (27c ) with potent MGAT2 inhibitory activity (IC50 = 7.8 nM) and excellent ADME-Tox profiles including metabolic stability, oral bioavailability, and CYP3A4 TDI. In a mouse oral fat tolerance test, compound 27c effectively and dose-dependently suppressed the elevation of plasma triacylglycerol levels after oral administration at doses of 1 and 3 mg/kg. We also discuss mitigation of the phototoxic liability of biaryl derivatives on the basis of the HOMO–LUMO gap hypothesis during the course of optimization efforts.